Professional Development of English Language Teachers in the Kingdom of Saudi Arabia in Light of the South Korean Experience: A Comparative Study - Almutairi, Hind Marzouq; Al-Jubair, Tahani Khalid (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to examine the professional development practices of teachers in South Korea and assess their potential applicability to the development of English language teachers in Saudi Arabia. The study population consisted of both countries (South Korea and Saudi Arabia), and the sample involved a comparison of professional development practices in each. The research employed a comparative method using George Bereday’s four-stage model: description, interpretation, juxtaposition, and comparison. The study identified similarities between the two countries, including the diversity of professional development programs offered to teachers. Among the key differences was the teaching load in South Korea, which does not exceed 17–18 classes per week. The study concluded with several recommendations to support the improvement of professional development for English language teachers. The study also recommended conducting additional comparative research on training programs for English language teachers in Saudi Arabia and other countries. Additionally, it presented a conceptual framework for digital professional learning communities designed for English language teachers, drawing on insights from international experiences.